Intensifikasi Pajak Hiburan Oleh Badan Pendapatan Daerah (BAPENDA) Kabupaten Bandung Barat - Catur Apriyanto; Sawitri Budi Utami (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Taxes are the largest component of the state's revenue source, so taxes have a crucial role in the Indonesian economy. The government in each year always strives so that tax revenue can always increase. This research is motivated by the realisation of entertainment tax revenue that did not reach the target in 2019, 2021 and 2022. The purpose of this study is to describe the efforts of Entertainment Tax intensification by the Regional Revenue Agency (Bapenda) of West Bandung Regency to increase entertainment tax revenue in West Bandung Regency. This research was conducted in West Bandung Regency, namely at the Regional Revenue Agency (BAPENDA) of West Bandung Regency. This research uses a qualitative descriptive method. The data collection techniques used are observation, interviews, and documentation. The data source of this research is primary data derived from the results of observations and interviews. Secondary data include tax and local tax revenue realisation, target data and realisation of entertainment tax revenue, and the number of entertainment taxpayers in West Bandung Regency. The main theory in this research is the theory of Local Tax Intensification from Kustiawan (2010). The results of this study indicate that the entertainment tax intensification activities of West Bandung Regency are still not well implemented and there are several obstacles. The obstacles that occur in this entertainment tax intensification activity are the lack of staff and limited human resources.